FAKTOR PREDIKTOR YANG MEMPENGARUHI KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI DI INDONESIA - Wahyu Puspitasari; Yati Afiyanti; Ida Farida (Nusantara Hasana Berdikari, 2021)
The incidence of hypertension is still one of the highest health problems in the health sector in Indonesia and around the world. Hypertension is often referred to as